Penggunaan Gaya Bahasa Dalam Kandayu Parawei - Eliani Eliani; Lazarus Linarto; Albertus Purwaka; Patrisia Cuesdeyeni; Yetebing Yetebing; Ana Listiani; Isti Prihatini (Bhinneka: Jurnal Bintang Pendidikan dan Bahasa, 2023)
The purpose of this study is to describe the use of language styles contained in Kandayu Parawei. The problems to be explored in this study are (1) what comparative language style is found in Kandayu Parawei, (2) what repetition language style is found in Kandayu Parawei, (3) what affirmative language style is found in Kandayu Parawei. This study uses a descriptive method, namely the content analysis method, namely collecting data by investigating, examining the contents of a poem, and literature study, namely collecting data by listening and reading. The data in this study are primary and secondary data, the primary data is in the form of verses of the Kandayu Parawei poem from the Kandayu collection, while secondary data is obtained through books relevant to the research title and the internet. Data collection techniques were carried out by reading and listening, then studying the contents of a poem needed as research data. The results of this study are the style of language contained in Kandayu Parawei (1) comparative language style: 1) personification and 2) hyperbole. (2) affirmative language style: 1) repetition and (3) repetition language style: 1) alliteration 2) mesodiplosis. The most dominant language style used in Kandayu Parawei is the repetition language style.